In the Eye of the Illusion: Variation in Perceptual Phenomena Within an Inverted Percept. (January 2017) - Deręgowski, Jan B.; Tatler, Benjamin W.
Monocular depth cues can lead not only to illusory depth in two-dimensional patterns but also to perspective reversals in three-dimensional objects. When a viewer perceptually inverts (reverses) a three-dimensional object, stimuli on the inner surfaces of that object also invert. However, the perceptual fate of anything occurring within the space that is enclosed by the walls of a perceptually reversible object is unknown. In the present study, perceptions of the relative vertical heights of stimuli within a truncated pyramidal chute were compared for stimuli placed laterally, on the inner surface of the chute, or centrally, suspended within the volume enclosed by the chute. The typical inversion was obtained for lateral stimuli, but central stimuli did not invert. While central stimuli maintained their veridical vertical order, participants experienced a considerable compression of perceptual depth. These results imply a dilution of the illusion within the centre of the volume of space that it encloses.